Penilaian Risiko Bendungan Manggar Dengan Metode Modifikasi ICOLD: Risk Assessment Manggar Dam With Modification ICOLD Method - Devi Ismijayanti; Robert J. Kodoatie; Sutarto Edhisono (Media Ilmiah Teknik Sipil, 2023)
Dam failure has fatal consequences. This is especially true for the infrastructures as well as population settling around the dam. Due to this reason, operation and maintenance of dams should put special care and attention on dam safety. Unfortunately, the budget allocated for dam operation and maintenance for many dams in Indonesia is still very limited. Therefore, it is necessary to determine the priority scale of maintenance or rehabilitation of dams based on its risk classification through a risk assessment. The risk assessment conducted for this research uses the modified ICOLD method. The modified ICOLD method is based on the results of a major inspection conducted in 2019. The results showed that Manggar Dam is categorized as a medium risk dam with a total risk score of 45. Recommended actions to minimize the risk of harm to dam failure included improved operations and maintenance management, improved quality of human resources managing dams, and improved reporting management